2020
DOI: 10.2337/dc19-1944
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Treatment Outcomes in Adults and Children With Type 1 Diabetes and Asymptomatic Celiac Disease: The CD-DIET Study

Abstract: To describe celiac disease (CD) screening rates and glycemic outcomes of a gluten-free diet (GFD) in patients with type 1 diabetes who are asymptomatic for CD. RESEARCH DESIGN AND METHODSAsymptomatic patients (8-45 years) were screened for CD. Biopsy-confirmed CD participants were randomized to GFD or gluten-containing diet (GCD) to assess changes in HbA 1c and continuous glucose monitoring over 12 months. RESULTSAdults had higher CD-seropositivity rates than children (6.8% [95% CI 4.9-8.2%, N 5 1,298] vs. 4.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…High rates of asymptomatic CD in patients with T1D have also been reported in the CD-DIET study by Mahmud et al which found that these patients with T1DCD can feel overwhelmed in managing the substantial lifestyle implications of both diseases despite facilitated access to no-cost care ( 6 ). Modified clinical approaches may well be needed to support families of asymptomatic children with CD, compared to children with symptomatic CD ( 19 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…High rates of asymptomatic CD in patients with T1D have also been reported in the CD-DIET study by Mahmud et al which found that these patients with T1DCD can feel overwhelmed in managing the substantial lifestyle implications of both diseases despite facilitated access to no-cost care ( 6 ). Modified clinical approaches may well be needed to support families of asymptomatic children with CD, compared to children with symptomatic CD ( 19 ).…”
Section: Discussionmentioning
confidence: 77%
“…Upon starting a GFD, several positive outcomes have been described in children with T1DCD including improvements in gastrointestinal symptoms, reduced number of hypoglycemic events and restoration of weight and growth ( 4 , 5 ). A recent study reports no differences in hemoglobin A1c over the first year of starting a GFD but provides evidence that a transition to a GFD is safe for children with T1D, with no differences in hypoglycemic time or adverse events ( 6 ). While health benefits from a GFD in children with T1DCD have been described, parents of these children have also reported significant challenges in managing both T1D and CD simultaneously including financial concerns and impact on mental/emotional health ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether or not a GFD reduces the risk of complications in those with type 1 diabetes and coeliac disease remains to be investigated. It is important to note that studies investigating whether or not individuals with asymptomatic type 1 diabetes benefit from a GFD report inconsistent results, and the long-term benefits of a GFD in asymptomatic children identified by routine screening have not been proven [ 7 10 ]. Therefore, screening for coeliac disease in asymptomatic children with coexisting type 1 diabetes, which may already be a burden, is still controversial [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brittle diabetes or unstable diabetes control should be thoroughly investigated for co-existing medical conditions. 7 Even though routine serologic screening test for CD in adult patients with T1DM yield no clinical benefits, 8 the possible co-existence of CD in T1DM patients must be kept in mind in unexplained hypoglycemia or other non-specific symptoms such as anemia, fatigue, paresthesia, infertility, amenorrhea, male impotence, and osteopenic bone disease. T1DM patients with undiagnosed CD have poor glycemic control and higher chance of diabetic complications.…”
Section: Discussionmentioning
confidence: 99%